EFFECT OF BACTERIAL BIOFERTILIZER AND COMPOST ON THE GROWTH OF TOMATO PLANT - & Al-Whaab, Salman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A pot experiment was conducted at Baghdad site for organic fertilizer  preparation  Plant Protection Directorate during summer of 2014-2015, using sandy Loam texture soil to study the effect of bacterial bio-fertilizer ( Azotobacter  chroococcum  and  Pseudomonas   fluorescens ) and  Compost  on  growth  and  nutrients  content  of  tomato  plants    "Super  queen". Eight treatments were used included  (Control , Azotobacter , pseudomonas, Azotobacter+ psuedomonas , Compost , Azotobacter + Compost  ,  Compost+  psuedomonas , Azotobacter +  psuedomonas + Compost). Complete  Randomized   Design ( CRD ) with 5 replicates was used. Results  showed  that  application of di bacterial  bio-fertilizer (AP) increased  significantly  dry mater weight  and N , P , K nutrients  content  for  shoots    with an increment of 36.4%,74.4%,76.0% and 64.9% respectively compared to control. Results  showed  that  application of di bacterial  bio-fertilizer (AP)  and compost  increased  significantly dry matter weight and N , P , K  nutrients content for shoot with increment  percentage of 95.3%  239.3% , 219.2% and 266.8%  respectively  compared  to  control.